Do biomass harvesting guidelines influence herpetofauna following harvests of logging residues for renewable energy?. Issue 3 (26th April 2016) - Fritts, Sarah; Moorman, Christopher; Grodsky, Steven; Hazel, Dennis; Homyack, Jessica; Farrell, Chris; Castleberry, Steven
Abstract: Forests are a major supplier of renewable energy; however, gleaning logging residues for use as woody biomass feedstock could negatively alter habitat for species dependent on downed wood. Biomass Harvesting Guidelines (BHGs) recommend retaining a portion of woody biomass on the forest floor following harvest. Despite BHGs being developed to help ensure ecological sustainability, their contribution to biodiversity has not been evaluated experimentally at operational scales. We compared herpetofauanal evenness, diversity, and richness and abundance of Anaxyrus terrestris and Gastrophryne carolinensis among six treatments that varied in volume and spatial arrangement of woody biomass retained after clearcutting loblolly pine ( Pinus taeda ) plantations in North Carolina, USA ( n = 4), 2011–2014 and Georgia ( n = 4), USA 2011–2013. Treatments were: (1) biomass harvest with no BHGs, (2) 15% retention with biomass clustered, (3) 15% retention with biomass dispersed, (4) 30% retention with biomass clustered, (5) 30% retention with biomass dispersed, and (6) no biomass harvest. We captured individuals with drift fence arrays and compared evenness, diversity, and richness metrics among treatments with repeated‐measure, linear mixed‐effects models. We determined predictors of A. terrestris and G. carolinensis abundances using a priori candidate N ‐mixture models with woody biomass volume, vegetation structure, and groundcover composition as covariates. We had 206 captures of 25 reptile species and 8710 captures of 17 amphibian species during 53 690 trap nights. Herpetofauna diversity, evenness, and richness were similar among treatments. A. terrestris abundance was negatively related to volume of retained woody biomass in treatment units in North Carolina in 2013. G. carolinensis abundance was positively related with volume of retained woody debris in treatment units in Georgia in 2012. Other relationships between A. terrestris and G. carolinensis abundances and habitat metrics were weak or absent. The lack of consistent community or population responses suggests the addition of a woody biomass harvest to a clearcut in pine plantations does not impact herpetofauna use of Coastal Plain loblolly plantations in the southeastern United States. We recommend additional research to examine relationships between woody biomass harvesting and rarer species or amphibians with high desiccation risk, particularly in other regions and harvesting systems.